Pelatihan Strategi Pemasaran Digital melalui Instagram dan Marketplace bagi Pelaku UMKM - Irvan Rolyesh Situmorang; Tigor Purba; Ydris Ydris; Willy Willy; Satria Satria (Eastasouth Institute, 2026)
This study examines the implementation of digital marketing strategy training through Instagram and marketplace platforms for micro, small, and medium enterprise (MSME) actors. The training aims to improve participants’ knowledge, skills, and adaptability in utilizing digital platforms for business promotion and sales optimization. The approach involved participatory training, practical simulations, and mentoring sessions. Data were collected through observation, questionnaires, and performance assessments. The findings indicate a significant increase in participants’ understanding of content creation, audience engagement, and online transaction management. The program also enhanced the participants’ confidence in adopting digital marketing strategies. This study contributes to community empowerment initiatives by demonstrating that structured digital marketing training can strengthen MSMEs’ competitiveness in the digital economy.